2004
DOI: 10.1097/01.ccm.0000142699.54266.d9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of N-acetylcysteine and deferoxamine on carbon tetrachloride-induced acute hepatic failure in rats

Abstract: Our data provide the first experimental demonstration that N-acetylcysteine plus deferoxamine reduces mortality rate, decreases oxidative stress, and limits inflammatory infiltration and hepatocyte necrosis induced by CCl4 in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 31 publications
4
45
0
4
Order By: Relevance
“…In fact, a number of papers reported the preventive effects of various antioxidants on the accumulation of lipid peroxidation products and on the increase in plasma transaminase activities induced by CCl 4 treatment. [10][11][12]14) In the present study, by assessing the effects of chitobiose and chitotriose on the amounts of lipid peroxidation products and the activities of plasma transaminases in CCl 4 -treated rats, we examined whether the 2 compounds could exert antioxidant activity when given orally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a number of papers reported the preventive effects of various antioxidants on the accumulation of lipid peroxidation products and on the increase in plasma transaminase activities induced by CCl 4 treatment. [10][11][12]14) In the present study, by assessing the effects of chitobiose and chitotriose on the amounts of lipid peroxidation products and the activities of plasma transaminases in CCl 4 -treated rats, we examined whether the 2 compounds could exert antioxidant activity when given orally.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] It is rational, therefore, to expect that antioxidative compounds can prevent CCl 4 hepatotoxicity. In fact, a number of papers reported the preventive effects of various antioxidants on the accumulation of lipid peroxidation products and on the increase in plasma transaminase activities induced by CCl 4 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of animals with CCl 4 causes severe hepatic injury, and CCl 4 is used to prepare an experimental model of ALF [Ritter et al, 2004;Terblanche and Hickman, 1991]. It is generally thought that CCl 4 toxicity is caused by the generation of a reactive intermediate, due to its reductive metabolism by hepatic CYP.…”
Section: Both Ho-1 Pre-induction and Biliverdin Ixa Treatment Can Prementioning
confidence: 99%
“…Among the antioxidant therapeutic interventions we find N-acetylcysteine (NAC) [9,11,12,14,15], deferoxamine (DFX) [13] and taurine [16]. In this regard, we have recently demonstrated that the combination of NAC and DFX is an effective treatment of severe sepsis in a rodent animal model [16], and in other models of inflammatory disease [15,[17][18][19]. Taurine is a naturally occurring free amino acid that has been shown to have neurotrophic and neuroprotective properties [20,21].…”
Section: Introductionmentioning
confidence: 98%